An investigation of prescription and over-the-counter supply of ophthalmic chloramphenicol in Wales in the 5 years following reclassification. (17th April 2013) - Du, Hank C T; John, Dai N; Walker, Roger
Abstract: Objectives: The aims of the study were to (i) quantify the sales of over-the-counter (OTC) ophthalmic chloramphenicol from all community pharmacies in Wales and investigate the impact on primary care prescriptions up to 5 years after reclassification and (ii) investigate the temporal relationship between items supplied OTC and on NHS primary care prescriptions. Methods: Primary care prescription data (2004–2010) and OTC sales data (2005–2010) for ophthalmic chloramphenicol were obtained. The quantity sold OTC was calculated from pharmacy wholesale records and sales data from a large pharmacy multiple. Spearman's rank correlation for prescription and OTC supplies of ophthalmic chloramphenicol was calculated for data from January 2008 to December 2010. Key findings: OTC supply of chloramphenicol eye drops and ointment were both highest in 2007–2008 and represented 68% (57 708/84 304) and 48% (22 875/47 192) of the corresponding prescription volume, respectively. There was a steady year-on-year increase in the combined supply of OTC ophthalmic chloramphenicol and that dispensed on prescription from 144 367 items in 2004–2005 to 210 589 in 2007–2008 before stabilising in 2008–2009 and 2009–2010. A significant positive correlation was observed between prescription items and OTC sales of chloramphenicol eye drops and ointment combined ( r = 0.7, P < 0.001). Conclusion: OTC availability increased the total quantity of ophthalmic chloramphenicol supplied in primary care compared to that seen prior to reclassification. Although growth in the sales of ophthalmic chloramphenicol OTC has stabilised and the supply pattern mirrors primary care prescribers, further work is required to investigate whether use is appropriate and whether the publication of updated practice guidance has changed this.